2017
DOI: 10.3832/ifor1722-009
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the field performance of Austrian pine seedlings using morphological attributes

Abstract: (2) , Mirko Škorić (1) This study examined whether the morphological attributes of Austrian pine (Pinus nigra ssp. nigra var. nigra Arnold) seedlings measured in the nursery could be used to forecast subsequent field performance over an extended time frame. Seedlings from three seed sources were produced in two types of containers and in bareroot seedbeds. These seedlings were measured for an array of morphological attributes (height, HT; root collar diameter, RCD; shoot height/diameter ratio, HD; shoot and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Under these environmental conditions, planting small seedlings is considered to be a conservative strategy that can be expedient insofar as planting shock is reduced by minimizing shoot water losses (Lamhamedi et al 1997, Trubat et al 2010, Cortina et al 2013, Ovalle et al 2016. Notwithstanding this, the specific literature on dry areas is somewhat contradictory, with studies showing that seedling size has positive , Villar-Salvador et al 2012, 2013b, Oliet et al 2013, Tsakaldimi et al 2013 or negative effects (Trubat et al 2008, Zida et al 2008, Cortina et al 2013, Ivetic et al 2016 or both (Navarro et al 2006) on planting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Under these environmental conditions, planting small seedlings is considered to be a conservative strategy that can be expedient insofar as planting shock is reduced by minimizing shoot water losses (Lamhamedi et al 1997, Trubat et al 2010, Cortina et al 2013, Ovalle et al 2016. Notwithstanding this, the specific literature on dry areas is somewhat contradictory, with studies showing that seedling size has positive , Villar-Salvador et al 2012, 2013b, Oliet et al 2013, Tsakaldimi et al 2013 or negative effects (Trubat et al 2008, Zida et al 2008, Cortina et al 2013, Ivetic et al 2016 or both (Navarro et al 2006) on planting performance.…”
Section: Introductionmentioning
confidence: 99%
“…A sturdiness quotient of less than 6 has been recommended as a desired characteristic of high-quality seedlings in tropical systems (Jaenicke 1999). Previous studies by several researchers have also found sturdiness quotient to correlate with seedling survival rate and initial growth following outplanting (Mexal and Landis 1990;Ivetić et al 2017). According to Takoutsing et al (2014), seedlings with sturdiness ratio greater than six were basically tall and thin (lanky) and etiolated, whereas a small quotient indicates sturdy plants with a higher chance of survival, particularly on windy or dry sites.…”
Section: Discussionmentioning
confidence: 75%
“…While RCD is positively and significantly correlated with both survival and growth after seedlings planting at the field, seedlings height can have both, positive and negative effect on seedlings field survival and growth, as reviewed by Ivetić and Devetaković [50]. Their combination as the HD (height/RCD) ratio was the most reliable plant attribute to forecast Austrian pine seedlings field performance [4] and there is evidence that initial seedling height and RCD are equally related to the field performance [3]. Our results show a consistent effect of seed colour on seedlings field growth of height and RCD.…”
Section: Discussionmentioning
confidence: 96%
“…The success of forest establishment program, including afforestation, reforestation, and forest restoration [1,2] mainly depends on the quality of Forest Reproductive Material (FRM), i.e., seedlings [3,4] and seeds [5]. FRM is often subjected to transfer and trade [6,7], emphasizing the genetic component of FRM quality regarding the seed source [8] and genetic diversity of seed lot used for production of seedlings in nursery or for direct seeding on the field [9].…”
Section: Introductionmentioning
confidence: 99%